Effect of Sunflower Crop Residue on Weed Suppression in Direct-Seeded Aus Rice Under Rice – Sunflower-Rice Cropping Pattern - Khatun, L; Chakrobarty, T; Zaman, MA; Nasim, M; Mondal, S (Bangladesh Agronomy Journal, 2022)
In Bangladesh direct-seeded Aus rice is a conventional rice cultivation practice and weed infestation is a severe problem in direct-seeded rice production due to the existence of favorable environment during this period. So, by minimizing the use of herbicides and replace them with eco-friendly and environmentally sustainable herbicides based on natural plant products or allelochemicals, a factorial experiment based on randomized complete block design with three replications was performed at the research field of Bangladesh Rice Research Institute (BRRI), Gazipur, Bangladesh from July 2018 to August 2019 to evaluate effect of sunflower crop residue on weeds growth and yield of direct seeded Aus rice in Transplanting Aman-Sunflower-Aus cropping pattern. Weed population and weed dry weight were significantly affected by crop residues treatment. Weed population was significantly lower in C3 (Direct sowing of Aus after 7 days of Sunflower residue incorporation) treatment than the control C1 (Direct sowing of Aus without Sunflower residue incorporation) treatment. The lowest weed dry weight (90.5 g m-2) was also obtained from C4 (Direct sowing of Aus after 14 days of Sunflower residue incorporation). The highest reduction of grain yield was obtained from without crop residue and no weeding treatments. The highest number of effective tillers m-2 (403.33), grain panicle-1 (114.67), tillers hill-1 (16.36), and grain yield (3.32 t ha-1) were observed from the treatments where sunflower residue was incorporated and the plots that were weed free. Results of this study indicate that sunflower residues showed potentiality to inhibit weed growth and it has a significant effect on the yield and yield parameters of direct seeded rice. Again weeds played a significant role in the reduction of yield of direct seeded rice. Thus, sunflower residues might be substitute for weed management practice as well as obtaining higher yield of direct seeded rice. Bangladesh Agron. J. 2021, 24(2): 115-125